Housing plus transportation affordability indices: Uses, opportunities, and challenges - Erick Guerra; Mariel Kirschen (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2016)
This technical paper provides an overview of the Center for Neighborhood Technology's (CNT) H+T affordability index and its potential application outside of the United States (US), where it has played a prominent role in documenting the relationship between housing and transportation and in influencing local and national housing policies. After describing the index and its policy use, we detail some of the challenges and opportunities of applying the index in Mexico, apply a modified H+T index to the Mexico City metropolitan area, and examine the effect of accounting for transportation costs on maps and measures of housing affordability. Finally, we conclude with a discussion of some of the opportunities and challenges of applying the H+T index in other OECD nations. The objective is to develop a better understanding of how an H+T index or similar tool could lead to improved public policy throughout the OECD.
Keywords: 330; Kommunale Verkehrspolitik; Wohnungspolitik; Wohnkosten; Fahrpreis; Mexiko-Stadt; Mexiko